2010
DOI: 10.1111/j.1749-7345.2010.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein and Lipid Levels on Growth and Body Composition of Subadult Olive Flounder, Paralichthys olivaceus, at a Suboptimal Water Temperature

Abstract: A 3 × 2 factorial experiment was conducted to investigate the proper dietary protein and lipid levels for growth of subadult olive flounder reared in suboptimal water temperature. Six diets were formulated to contain three levels of protein (40, 45, and 50%) and two levels of lipid (7 and 14%). Triplicate groups of fish (initial body weight of 255 g) were hand‐fed to apparent satiation for 14 wk in suboptimal water temperature (15.5 ± 1.3 C). The highest weight gain and feed efficiency were observed in fish fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…This probably resulted from differences in fish size, water temperature, and/or the duration of feeding trials among the studies. SGR (0.22%/day) of grower olive flounder in the 12WF-C treatment in this study was comparable to that (0.20%/day) of grower fish averaging 287 g fed a commercial diet to satiation once a day at a mean temperature of 12.1°C for 15 weeks (Kim et al, 2009) and within values (0.18-0.56%/day) obtained from grower fish averaging 255 g fed diets containing various protein and lipid levels daily at 15.5°C for 14 weeks (Kim et al, 2010). Therefore, growth of grower olive flounder in the 12WF-C treatment in this study seemed to be relatively well achieved.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…This probably resulted from differences in fish size, water temperature, and/or the duration of feeding trials among the studies. SGR (0.22%/day) of grower olive flounder in the 12WF-C treatment in this study was comparable to that (0.20%/day) of grower fish averaging 287 g fed a commercial diet to satiation once a day at a mean temperature of 12.1°C for 15 weeks (Kim et al, 2009) and within values (0.18-0.56%/day) obtained from grower fish averaging 255 g fed diets containing various protein and lipid levels daily at 15.5°C for 14 weeks (Kim et al, 2010). Therefore, growth of grower olive flounder in the 12WF-C treatment in this study seemed to be relatively well achieved.…”
Section: Resultssupporting
confidence: 77%
“…The dietary optimum protein and lipid levels for growth of grower olive flounder were 45% and 14%, respectively, which were equivalent to an estimated energy level of 17.4 kJ/g diet when fish averaging 255 g were fed 40, 45, and 50% protein diets with two lipid levels (7 and 14%) to satiation twice daily at a mean temperature of 15.5°C for 14 weeks (Kim et al, 2010). Supplementation of both protein and lipid levels in the diet (HPL diet) achieved compensatory growth of grower fish in this study, partially agreeing with Cho and Heo's (2011) study reporting that a diet containing a combined protein and lipid level effectively improved compensatory growth of juvenile olive flounder at optimum temperature, but a diet containing the combined protein and lipid level with 5% amino acid supplementation did not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, in the previous study (Akpınar et al 2011), we observed that in shi drum, low dietary protein diets with low protein/energy ratio were consumed more than high-protein diets. An alternative explanation of the increase in FI, although still not clearly understood phenomenon, may be a hyperphagic response in fish to energy-rich diets as observed in European sea bass (Peres and Oliva-Teles 1999;2001), olive flounder (Paralichthys olivaceus) (Kim et al 2010), and kelp grouper (Epinephelus bruneus) (Yoshii et al 2010). Yet, the lipid level range employed in this study was narrow, and the highest level may have been not enough to create a significant reduction in FI.…”
Section: Discussionmentioning
confidence: 97%
“…However, several studies report that increasing dietary lipid within a certain limit can improve the growth and protein utilization of fish through the protein sparing effect by lipid (Peres and Oliva-Teles, 1999;López et al, 2009;Kim et al, 2010), where dietary lipid is used as the main energy source in the overall energy expenditure while dietary protein is utilized for growth (Xu et al, 2001). On the contrary, limited or no protein sparing effect is also reported in many fish species such as grass carp Ctenopharyngodon idella, tiger puffer Takifugu rubripes and turbot Psetta maxima where increasing levels of dietary lipid did not bring any beneficial effects on growth, protein efficiency ratio and feed utilization but resulted in a significant lipid accumulation in the body (Regost et al, 2001;Du et al, 2005;Kikuchi et al, 2009 …”
Section: Introductionmentioning
confidence: 99%